2019
DOI: 10.1016/j.jcv.2019.104200
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genetic variability of respiratory syncytial virus in Portugal, 2014–2018

Abstract: A B S T R A C TIntroduction: Respiratory syncytial virus (RSV) is associated with substantial morbidity and mortality since it is a predominant viral agent causing respiratory tract infections in infants, young children and the elderly. Considering the availability of the RSV vaccines in the coming years, molecular understanding in RSV is necessary. Objective: The objective of the present study was to describe RSV epidemiology and genotype variability in Portugal during the 2014/15-2017/18 period. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 54 publications
4
18
0
Order By: Relevance
“…24 In Portugal, a study of 6743 samples analyzed through the influenza surveillance system (2014-2018) in children aged <5 years found that 72.5% were positive for RSV. 20 Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged <5 years, which is consistent with our findings. Also, Hall et al…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…24 In Portugal, a study of 6743 samples analyzed through the influenza surveillance system (2014-2018) in children aged <5 years found that 72.5% were positive for RSV. 20 Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged <5 years, which is consistent with our findings. Also, Hall et al…”
Section: Discussionsupporting
confidence: 92%
“…To increase accuracy for RSV potential cases, as is described in temperate climates, 2 , 19 data were analyzed by epidemic season (November to March 20 ) in 2015/2016, 2016/2017, and 2017/2018, except for the analyses of date of birth and weekly evolution of RSV cases, which were done for the total study population.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid substitutional changes that were mentioned earlier in the results section (i.e., from T227N to T312I) were also reported by Abou-El-Hassan et al, Tsergouli et al,Yun et al,[26][27][28]. The circulating genotypes from different countries during the same period of our study (i.e., 2016, 2017, and 2018) were found to be of GB5.0.5a lineage of GB5 genotype in South Korea, Portugal, Greece, Australia, Saudi Arabia, Lebanon, and Thailand [18,[26][27][28][36][37][38]. In India, according to the old classification, previous studies reported circulation of BA genotype (2001)(2002)(2003)(2004)(2005), BA7, BA9, BA10, BA12 genotypes (2007-2010), SAB4, BA8, and BA9 genotypes (2011)(2012)(2013)(2014)(2015) in Delhi; BA genotype (2005 -2008) in Kolkata; GB2, BA9, and BA12 genotypes (2009-2012) in Maharashtra; BA9 and BA10 genotypes (2012)(2013)(2014) in Kerala [14,22,23,39,40,42].…”
Section: Discussionsupporting
confidence: 87%
“…The amino acid substitutional changes that were mentioned earlier in the results section (i.e., from L248I to T320A) were also reported by Cui et al, Ogunsemowo et al, Malasao et al, and Eshaghi et al [ 32 35 ]. Few of the newly identified substitutional changes were also observed in our study sequences, but these changes did not constitute for defining these sequences as novel genotype based on the classification criteria defined by Goya et al The circulating genotypes from different countries during the same period of our study (i.e., 2016, 2017, and 2018) were replicated same as our findings as GA2.3.5 lineage of GA2 genotype in South Korea, Portugal, Greece, Australia, Saudi Arabia, Lebanon, and Thailand [ 18 , 26 28 , 36 38 ]. In India, according to old classification previous studies reported circulation of GA2, GA5 genotypes (2001–2005), and ON1 genotype (2011–2015) in Delhi; GA5 and NA1 genotypes (2009–2012) in Assam; and NA1 lineage and ON1 genotypes in Pune (2009–2012), and NA1 and ON1 genotypes in Kerala (2012–2014) [ 14 , 22 , 23 , 30 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 72%
“…Structural and evolutionary analyses of MYC2/3/4 coding sequences in the U's triangle species were conducted with homologous sequences on Brassica database (http://brassicadb.cn/#/BLAST/) according to the neighbor-joining method (Tarahomi et al, 2020) using molecular evolutionary genetics analysis software (MEGA7 software) (Kumar et al, 2016). The main parameter settings were distance model, p-distance method (Sáez-López et al, 2019), gene tree robustness detection, bootstrap test (1,000 replicates) (Elateek et al, 2020), processing of gap missing data, and deletion between pairs.…”
Section: In-silico Analysesmentioning
confidence: 99%